Determinação da eficiência de drenagem para um pavimento intertravado de concreto permeável sob diferentes intensidades de precipitação - (:unkn) unknown (Universidade Federal do Pampa, 2016)
One of the major disorders encountered by the population of urban centers stems from urban sprawl, which brings with it an increase in impermeable areas, changing the water infiltration conditions in the soil and thus causing increased runoff volume. In this way, it has been researching alternative ways to provide the cities conditions closer to those existing before the urbanization process. One of the search objects is the permeable paving, since it enables excellent drainage conditions, thus contributing to reducing runoff . This study aims to verify the efficiency of drainage of interlocked block permeable concrete under different conditions of precipitation. The experiment was conducted on the premises of the Federal University of Pampa, Campus Alegrete. Previously, it was sought to the literature, the infiltration capacity for the study area. Afterward, It was determined the intensity of maximum rainfall, through the heavy rain equations with parameters adjusted for the city of Alegrete, having been adopted in the experiments a return time of 10 years and duration of 15 minutes. It was simulated an intense precipitation approach the calculated value and other simulation with lower intensity, both with three replications, thus analyzing the behavior of the material tested under different intensities of rainfall. For the experiments, it was first built a rain simulator able to simulate different intensities used. The Rainfall was applied in a m² experimental area with a slope of 5%, seated on the stone reservoir with total infiltration system, previously scaled. To obtain the data, it was performed from a reservoir feeding system at the time the test was started. The same procedure was given at the end of each experiment, so knowing the volume of applied rainfall. The experimental module also contained a collection system where the drained volume was directed to a container for determining the generated flow. For each test performed, determine the soil humidity content in order to correlate the flow rates generated with soil conditions. The results show that the permeable concrete floors have interlocked flow coefficient less than the most widely used flooring systems, stripping their use in appropriate locations to provide a good alternative in the search for reducing runoff. For the city Alegrete, due to low soil infiltration capacity, the total infiltration system can be modified for the partial system with the use of drains, thus providing improved performance. However, even with the infiltration capacity presented by the soil, the use of interlocked floor permeable concrete to show how good alternative paving due to provide more efficient drainage conditions than conventional floors, with values close to unpaved areas like grass or exposed soil.
Keywords: Civil engineering; Drainage; Runoff; Permeable paving; Engenharia civil; Drenagem; Escoamento superficial; Pavimento Permeável; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL